2023
DOI: 10.3389/fonc.2023.1250558
|View full text |Cite
|
Sign up to set email alerts
|

Immune signatures of the POLE mutation in endometrial carcinomas: a systematic study based on TCGA data and clinical cohort validation

Tieyan Wang,
Dan Yu,
Juanjuan Wang
et al.

Abstract: BackgroundPOLE is a critical biomarker for endometrial cancer (ECs) prognosis and therapeutic decision. However, the immune infiltration and immunotherapy-related gene expression in the tumor microenvironment (TME) of POLE-mutated ECs remain unresolved.MethodsThe TCGA database was used to characterize the TME of POLE mutants, which primarily included immune cells and co-expression genes. We used immunohistochemistry (IHC) to determine immune cell abundance and PD-L1 expression in 104 EC tissues, including 11 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…26 Furthermore, within POLE-mutated ECs, there is an upregulation of immune checkpoint molecules and regulatory T cell markers, including LAG3, TIM-3, TIGIT, PD-1, CTLA-4, and FOXP3, potentially as a result of immune evasion caused by prolonged exposure to antigens. 27 This implies that immune checkpoint inhibitors hold potential for a subset of patients with recurrent or metastatic POLE-mut ECs. [27][28][29][30][31] Nevertheless, the factors contributing to the absence of heightened immune responses in certain POLE-mut patients remain unclear, including whether it is attributed to a low mutation burden or other immune evasion mechanisms.…”
Section: Clinical and Pathological Features Of Pole-mutated Endometri...mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Furthermore, within POLE-mutated ECs, there is an upregulation of immune checkpoint molecules and regulatory T cell markers, including LAG3, TIM-3, TIGIT, PD-1, CTLA-4, and FOXP3, potentially as a result of immune evasion caused by prolonged exposure to antigens. 27 This implies that immune checkpoint inhibitors hold potential for a subset of patients with recurrent or metastatic POLE-mut ECs. [27][28][29][30][31] Nevertheless, the factors contributing to the absence of heightened immune responses in certain POLE-mut patients remain unclear, including whether it is attributed to a low mutation burden or other immune evasion mechanisms.…”
Section: Clinical and Pathological Features Of Pole-mutated Endometri...mentioning
confidence: 99%
“…27 This implies that immune checkpoint inhibitors hold potential for a subset of patients with recurrent or metastatic POLE-mut ECs. [27][28][29][30][31] Nevertheless, the factors contributing to the absence of heightened immune responses in certain POLE-mut patients remain unclear, including whether it is attributed to a low mutation burden or other immune evasion mechanisms. A study examining early-stage low-grade EC identified five distinct immunotypes that exhibited superior sensitivity and specificity in predicting recurrence.…”
Section: Clinical and Pathological Features Of Pole-mutated Endometri...mentioning
confidence: 99%